Phytoextraction of heavy metal polluted soils using Sedum plumbizincicola inoculated with metal mobilizing Phyllobacterium myrsinacearum RC6b - Ma, Ying (2013)
The aim of this study was to investigate the effects of metal mobilizing plant-growth beneficial bacterium Phyllobacterium myrsinacearum RC6b on plant growth and Cd, Zn and Pb uptake by Sedum plumbizincicola under laboratory conditions. Among a collection of metal-resistant bacteria, P. myrsinacearum RC6b was specifically chosen as a most favorable metal mobilizer based on its capability of mobilizing high concentrations of Cd, Zn and Pb in soils. P. myrsinacearum RC6b exhibited a high degree of resistance to Cd (350 mg L 1), Zn (1000 mg L 1) and Pb (1200 mg L 1). Furthermore, P. myrsinacearum RC6b showed multiple plant growth beneficial features including the production of 1-aminocyclopropane-1-carboxylic acid deaminase, indole-3-acetic acid, siderophore and solubilization of insoluble phosphate. Inoculation of P. myrsinacearum RC6b significantly increased S. plumbizincicola growth and organ metal concentrations except Pb, which concentration was lower in root and stem of inoculated plants. The results suggest that the metal mobilizing P. myrsinacearum RC6b could be used as an effective inoculant for the improvement of phytoremediation in multi-metal polluted soils.